1932
DOI: 10.1139/cjr32-090
|View full text |Cite
|
Sign up to set email alerts
|

Note on an Investigation Into the Fluorescence of Hairs Infected by Certain Fungi

Abstract: 1. Observations under filtered ultra-violet light of the available material of Microsporon audouini, M. felineum, Trichophyton gypseum, T. violaceum, T. album and Achorion schoenleini indicate that the species belonging to the genera Microsporon and Achorion produce an intense green fluorescence in the substance of hairs infected by them. Trichophyton-infected hairs appear a paler bluish-white. Normal pigmented hairs appear dark.2. It is shown that the spores and hyphae of the fungus whether within or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1935
1935
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…He stated that microscopic examination of hairs infected by Microsporon showed that the fungus itself was fluorescent, and also that the fluorescence was retained indefinitely when the hairs were placed in potash. Davidson and Gregory (1932) confirmed the results of the previous workers who showed that the presence or absence of green fluorescence is determined by the species of fungus present. Green fluorescence was observed in hairs infected by Microsporon audouini, M .…”
Section: Trichophyton Granulosum Trichophyton Interdigitalesupporting
confidence: 91%
See 1 more Smart Citation
“…He stated that microscopic examination of hairs infected by Microsporon showed that the fungus itself was fluorescent, and also that the fluorescence was retained indefinitely when the hairs were placed in potash. Davidson and Gregory (1932) confirmed the results of the previous workers who showed that the presence or absence of green fluorescence is determined by the species of fungus present. Green fluorescence was observed in hairs infected by Microsporon audouini, M .…”
Section: Trichophyton Granulosum Trichophyton Interdigitalesupporting
confidence: 91%
“…Vigne (1927) and Margarot and Devbze (1929) believed that the fluorescence observed was that of the fungus itself, and attributed the faintness of the luminosity of the endothrix trichophyta to the obscuring of the fluorescence by the hair-keratin surrounding hyphae and spores. Davidson and Gregory (1932) questioned this explanation on the ground that hairs infected by the ectothrix species, T. gypseum and T. clbum do not show green fluorescence, while favus hairs, in which the hyphae occupy an endothrix position, fluoresce with a green light. They considered that the fluorescence was situated in the hair rather than in the fungus.…”
Section: Trichophyton Granulosum Trichophyton Interdigitalementioning
confidence: 99%
“…These ob¬ servations confirm the belief of Davidson and Gregory that fluorescence is confined only to \ l = l a t c l i c k \ References 2 and 4. that portion of the hair which is actually in¬ vaded. 12 Benedek,13 on the other hand, con¬ sidered that the spore sheath was necessary for the development of fluorescence, a view with which I am in disagreement.…”
Section: Audouini Infectionsmentioning
confidence: 99%
“…The initial extract from the infected hair is a complex mixture of breakdown products of keratin and, presumably, other metabolic products from the invading fungus. Separation from ninhydrin-reacting substances by the techniques described was not complete and it is still an open question as to whether the main fluorescent substance is a peptide; Davidson & Gregory (1932) reported no ninhydrin-reacting material in their extracts, while Robinson et al (1953) concluded from infra-red analysis of their extract from M . audouini infected hair, that the material resembled a peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Davidson & Gregory (1932) showed that it could be readily extracted from the hairs by hot water and, working with a crude extract, they showed the presence of a substance or substances containing nitrogen, phenolic and aldehyde groups but no ninhydrin-reacting substances. Felsher (1949) extracted the hairs with cold 2~-sodium bromide and showed colour changes of the fluorescence with pH, and quenching by a number of salt solutions.…”
mentioning
confidence: 99%